Design and implementation of cubic spline interpolation for spike sorting microsystems - Tung-Chien Chen; Yun-Yu Chen; Tsung-Chuan Ma; Liang-Gee Chen (2011 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP), 2011)
Accurate spike sorting is important for neuroscientific and neuroprosthetic applications. The sorting of spikes depends on the features extracted from the neural waveforms, and a better sorting performance usually comes with a higher sampling rate (SR). However for long duration experiments on free-moving subjects, the miniaturized and wireless neural recording ICs are the current trend. The compromise on sorting accuracy is usually made for the low power consumption with a lower SR. In this paper, the VLSI architecture of cubic spline interpolation is proposed to improve the power-accuracy tradeoff for the spike sorting microsystems. The window-based interpolation schedule, event-triggered processing, and two-step interpolation scheme are applied to save the memory and computation. 0.04 μW/channel is finally achieved after the implementation in 90 nm process.